Menumbuhkan Sikap Gemar Membaca Alkitab Pada Siswa Kelas 8 Sekolah Menengah Pertama BOPKRI 3 Yogyakarta - Junita Purba; Bobby Kurnia Putrawan; Ruthnawaty Setiawan; Dian Paskarina Tindoilo; Juan Ananta Tan (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2024)
This study aims to foster an attitude of liking to read the Bible in grade 8 students of SMP BOPKRI 3 Yogyakarta. The attitude of liking to read the Bible is an important aspect in religion-based character education in this school. The research method used is classroom action research (CAR) which consists of several cycles. Each cycle includes planning, implementation, observation, and reflection. The results of the study indicate that by using interactive and interesting learning methods, such as group discussions, shared reading, and the use of digital media, there is a significant increase in interest and frequency of reading the Bible among students. In addition, support from teachers, parents, and the school environment also plays an important role in encouraging this reading attitude. This study concludes that applying varied and collaborative learning methods effectively fosters an attitude of liking to read the Bible in grade 8 students. Recommendations for further research are to expand the methods used and involve more participation from the school community to create a stronger reading culture. Penelitian ini bertujuan untuk menumbuhkan sikap gemar membaca Alkitab pada siswa kelas 8 SMP BOPKRI 3 Yogyakarta. Sikap gemar membaca Alkitab merupakan aspek penting dalam pendidikan karakter berbasis agama di sekolah ini. Metode penelitian yang digunakan adalah penelitian tindakan kelas (PTK) yang terdiri dari beberapa siklus. Setiap siklus meliputi perencanaan, pelaksanaan, observasi, dan refleksi. Hasil penelitian menunjukkan bahwa dengan menggunakan metode pembelajaran yang interaktif dan menarik, seperti diskusi kelompok, pembacaan bersama, serta penggunaan media digital, terjadi peningkatan signifikan dalam minat dan frekuensi membaca Alkitab di kalangan siswa. Selain itu, dukungan dari guru, orang tua, dan lingkungan sekolah juga berperan penting dalam mendorong sikap gemar membaca ini. Kesimpulan dari penelitian ini adalah bahwa penerapan metode pembelajaran yang variatif dan kolaboratif efektif dalam menumbuhkan sikap gemar membaca Alkitab pada siswa kelas 8. Rekomendasi untuk penelitian selanjutnya adalah memperluas metode yang digunakan serta melibatkan lebih banyak partisipasi dari komunitas sekolah untuk menciptakan budaya membaca yang lebih kuat.